2012
DOI: 10.1007/s13197-012-0840-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified atmosphere packaging and storage conditions on quality characteristics of cucumber

Abstract: Cucumbers (Cucumis sativus L.) stored in perforated modified atmosphere packaging (MAP) under cold room (4±1°C and 90±2 % RH) and ambient condition (23-26°C and 63-66 % RH) were evaluated for firmness, weight loss (WL), colour, chilling injury and sensory characteristics. The firmness of cucumbers was decreased to 0.333 and 0.326 N on 6th and 12th day of storage, respectively from initial value of 0.38 N. After 12 days of storage, the WL was in the range of 1.62-12.89 % whereas the cucumber stored under MAP ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 17 publications
4
24
0
Order By: Relevance
“…In the present study, fruits in all treatments showed an increasing trend for weight loss during storage, but MAP was found to be effective in the prevention of weight loss. The ability of MAP to prevent weight loss was previously reported by several researchers for various fruits (Caleb et al, 2013;Dhall et al, 2012;Kahramano glu et al, 2018) and for cucumber fruits (Manjunatha and Anurag, 2014;Wang and Qi, 1997). In addition, application of PEx and LO was found to reduce weight loss of cucumber fruit, in agreement with previous studies carried out on different fruits (Kahramano glu 2019;Kahramano glu et al, 2018;€ Ozdemir et al, 2010;Prakash et al, 2015;Zahid et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, fruits in all treatments showed an increasing trend for weight loss during storage, but MAP was found to be effective in the prevention of weight loss. The ability of MAP to prevent weight loss was previously reported by several researchers for various fruits (Caleb et al, 2013;Dhall et al, 2012;Kahramano glu et al, 2018) and for cucumber fruits (Manjunatha and Anurag, 2014;Wang and Qi, 1997). In addition, application of PEx and LO was found to reduce weight loss of cucumber fruit, in agreement with previous studies carried out on different fruits (Kahramano glu 2019;Kahramano glu et al, 2018;€ Ozdemir et al, 2010;Prakash et al, 2015;Zahid et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…EOs (i.e., cinnamon oil) and chitosan have previously been tested and reported to have inhibitory effects on fungal rot and prevent weight loss on cucumber fruits (Carmo et al, 2008;de Sousa et al, 2012). Cold storage at 5°C (Wang and Zhu, 2017), short-term hot water application (Nasef, 2018), ozone treatment (Glowacz et al, 2015), and MAP (Manjunatha and Anurag, 2014) were also tested and found to be effective in preventing cucumber senescence. To the best of the authors' knowledge, no previous studies have been conducted on the effects of LO and propolis on the postharvest quality of cucumber fruits.…”
mentioning
confidence: 99%
“…They were sorted to discard those with any signs of decay and visible defects. The cucumbers used for further experiments were stored at 10 °C for one day [26]. Figure 1 depicts the cucumber species used in this study, being similar to the one studied by Dan et al [27].…”
Section: Methodsmentioning
confidence: 99%
“…Usually, consumer judges the cucumber quality on the basis of freshness and appearance at the purchase time. Cucumbers are a highly perishable commodity and susceptible to low temperatures below 7 o Cwhichresults ina lot of biochemical and physiological processes such as water loss, surface pitting, discoloration, cell wall degradation, membrane damage, production of reactive oxygen species andripening and senescence (Hakim et al, 1999 andTsuchida et al, 2010), particularly when the temperature is raised after exposure to low temperature (Manjunatha and Anurag, 2014). These processes deteriorate the quality and shorten shelf life of cucumbers.…”
Section: Introductionmentioning
confidence: 99%